Clustering of the Federal Subjects of the Russian Federation by Deposit Risk Level - Lunyakova, Natalya Avtandilovna; Lavrushin, Oleg Ivanovich; Lunyakov, Oleg Vladimirovich (Economy of Regions, 2018)
The research is focused on the evaluation of regional differences by the level of deposit risk. Deposit risk is connected with resources sustainability of regions and can constrain the transformation of attracted deposits into credit and investment resources. The literature review shows that previous works were primarily focused on deposit risks at the micro level, that is, at the level of a bank. The Bank of Russia uses the same inductive approach to assess the financial sustainability and development prospects of credit institutions at the regional and national levels. However, the execution of prudential regulations by banks, in particular, liquidity ratios, does not allow to make a precise estimation of the differences among regions in terms of deposit risk. The presence of imbalances in the territorial concentration of credit institutions can affect the volatility and cost of deposit resources. The purpose of this paper is to improve the scientific and methodological approaches for assessing deposit risk. For this purpose, we propose to use cluster methods for classifying the regions based on the revealed internal links between deposit risk indicators. In contrast to previous scientific works, we offer to use semi-dispersion for calculating the volatility of deposits. The volatility of deposits can be interpreted as a measure of adverse downside risk. Furthermore, we propose the nominal scale to distinguish the different level of deposit risk. The research results confirm that there is a nonlinear linkage between the territorial concentration of credit organizations, level of provision of regions with banking services as well as volatility of deposits at the level of regions. We have revealed that the concentration of banking business in all regions is more closely connected with the sustainability of bank resources. The scientific approach to deposit risk evaluation presented in the paper expands the system of indicators for the development of the economy of regions. This approach can be used for both the monitoring of the financial and economic development of the regions of the Russian Federation and the macroeconomic forecasting.